PEDAGOGICAL SIGNIFICANCE OF FINE ARTS IN THE FORMATION OF CREATIVE AND AESTHETIC COMPETENCES IN STUDENTS - Abduxamidov Quvonchbek Yangiboy o‘g‘li (Modern American Journals, 2025)
This article analyzes the role of fine arts in the development of creative and aesthetic competencies in higher education students (professional-pedagogical direction), pedagogical methods and techniques. As can be seen from the analysis of the literature, project-based approaches, interactive classes and the use of digital tools in modern art education significantly increase students' creativity and aesthetic taste. The study used qualitative and quantitative methods, and the results of questionnaires, interviews and observations were analyzed.
Keywords: Fine arts, creative competence, aesthetic education, pedagogical approach, innovative methods